Clinical practice guidance for the management of fetal growth restriction: an expert review - Cecilia Villalaín; Ignacio Herraiz; Ranjit Akolekar; Francesc Figueras; Fatima Crispi; Giuseppe Rizzo; Ilenia Mappa; Manel Mendoza; Teresa del Moral; Tamara Stampalija; Tullio Ghi; Alberto Galindo (The Journal of Maternal-Fetal & Neonatal Medicine)
Background Fetal growth restriction (FGR) is associated to increased perinatal morbidity and mortality. Prenatal identification and subsequent intervention can improve outcomes. Our aim was to provide recommendations of the management of FGR reaching all possible scenarios (high-income and low-middle-income countries, referral as well as referring centers) but not to stablish a universal standard of care.Methods an organizational committee assigned a panel of experts’ different topics regarding clinical practice management of FGR. Evidence was prioritized according to the GRADE classification system, with the highest levels of evidence given the greatest weight and organized in practical approach. Although most diagnostic, screening and management options are described, our aim is not to recommend all but to highlight the evidence for each one and give our recommendations for their use understanding that not all settings will have every option available.Results We provide a practical approach to allow optimization of timing and mode of delivery in order to avoid unnecessary or excessive interventions and improve perinatal outcomes.Conclusion This document aims to provide guidance for the clinical management of pregnancies with suspected FGR.